Female Political Representation in EAC States - Bagi, Judit (Afrika Tanulmányok / Hungarian Journal of African Studies, 2019)
Almost all East African Community (EAC) member states have more than 30 percent female MPs in their national parliaments: Rwanda (61.3%), Tanzania (37.2%), Burundi (36.4%), Uganda (34.3%), Kenya (21.8%), and South Sudan (28.5%). What could be the reason for the fact that all EAC countries, except Kenya, are above the so-called ‘critical mass’ in the field of female political representation? In the last decades, both conflict and political transition have emerged in EAC countries. During the post-conflict period, gender norms and values (with a focus on gender quota regulations) have been implemented into national policies. The newly established liberal constitutions and gender policy creation have affected the status of East African women positively, although there is a big difference between the states concerning the effectiveness of gender policy-making. My paper (with the help of my field trips in Arusha and Kigali in 2015 and 2016) intends to contribute to a better understanding of EAC countries in transition, with an emphasis on the changing role of women in society, particularly in the important fields of gender politics and political representation.